PROTOTYPE APLIKASI PENGOLAHAN DATA DISTRIBUSI TABUNG OKSIGEN PADA PT. BUDI NABATI PERKASA: System;Data;Application;Prototype. - Adhiatma, Novri; Ikhsan, Muhammad; Tamrinsyah; Fauzy Bin Willy , Mohd (FORTECH (Journal of Information Technology), 2021)
During this time, the system that is currently running at a company is in the process of circulating oxygen cylinders; the recording is still done manually, including incoming and outgoing goods transactions. The Calculation of stock of goods, sales and report making, only recorded in the general ledger. In the old system, there are still often errors, both in calculations and in reporting. Prototype of Oxygen Cylinder Distribution Data Processing Application at PT. Budi Nabati Perkasa, this system is made using a computerized application and aims to make it easier for admin in recording sales and goods transactions so that the process of making reports can be calculated automatically. This system can minimize the occurrence of errors in the process of data recap or manufacture of the report.